In the shadow of the towers : speculative fiction in a post-9/11 world - Lain, Douglas (2015)
"In the Shadow of the Towers compiles nearly twenty works of speculative fiction responding to and inspired by the events of 9/11, from writers seeking to confront, rebuild, and carry on, even in the face of overwhelming emotion. Writer and editor Douglas Lain presents a thought-provoking anthology featuring a variety of award-winning and best-selling authors, from Jeff VanderMeer (Annihilation) and Cory Doctorow (Little Brother) to Susan Palwick (Flying in Place) and James Morrow (Towing Jehovah). Touching on themes as wide-ranging as politics, morality, and even heartfelt nostalgia, today's speculative fiction writers prove that the rubric of the fantastic offers an incomparable view into how we respond to tragedy. Each contributor, in his or her own way, contemplates the same question: How can we continue dreaming in the shadow of the towers? "--
Keywords: Science fiction, American -- 21st century; September 11 Terrorist Attacks, 2001 -- Fiction; FICTION / Science Fiction / Short Stories